The Changing Epidemiology of Hepatocellular Carcinoma : Experience of a Single Center. (27th February 2020) - Giannitrapani, Lydia; Zerbo, Maddalena; Amodeo, Simona; Pipitone, Elisa; Galia, Massimo; Li Cavoli, Tancredi Vincenzo; Minissale, Maria Giovanna; Licata, Anna; Schiavone, Cosima; Brancatelli, Giuseppe; Montalto, Giuseppe; Soresi, Maurizio
Abstract : Aims . To analyze the main etiological factors and some clinical features of patients with hepatocellular carcinoma (HCC) at diagnosis and to compare them with those we described ten years ago. Materials and Methods . We compared two groups of patients with HCC, Group 1 consisting of 132 patients (82 M, 50 F) diagnosed in the 2003–2008 period and Group 2 including 119 patients (82 M, 37 F) diagnosed in the 2013–2018 period. For all patients, age, sex, viral markers, alcohol consumption, serum alpha-fetoprotein (AFP) levels, and the main liver function parameters were recorded. The diagnosis of HCC was based on AASLD, EASL guidelines. The staging was classified according to the "Barcelona Clinic Liver Cancer staging system" (BCLC). Results . Mean age was 69.0 ± 8 years in Group 1 and 71.0 ± 9 in Group 2 (P < 0.05 ). HCV subjects were significantly older in Group 2 (P < 0.05 ), and there was no difference for those with other etiologies. The main etiology in the two groups was HCV 80% (Group 1) versus 73% (Group 2) (P = ns ), and there was no difference for HBV. Nonviral etiology was higher in Group 2 versus Group 1 (17% versus 9%; P < 0.05 ). The Child class at diagnosis showed no difference between the two groups, whereas in Group 2 the HCC staging according to BCLC was less severe (P < 0.02 ). When comparing the viral versus post-NASH BCLC in patients of the second period alone, the staging was more severe in the latter (P < 0.01 ). AFP serum levels were normal in 37% of cases in Group 1 and in 67% in Group 2 (P < 0.0001 ) and were less frequently diagnostic in post-NASH than in other etiologies (P < 0.03 ). Conclusions . This study shows that over the last decade a number of features of patients with HCC in our region have changed, particularly age at onset, etiological factors, and staging of HCC.